HUMAN RIGHTS PROTECTION FROM THE PERSPECTIVE OF THE 1991 CONSTITUTION OF MACEDONIA - Körbayram, Azam; Hoca, Elif (International Scientific Journal Vision, 2021)
Human rights have been a topic of conversation since ancient times, and for many years there has been a struggle for their guarantee. Almost all states have led to fierce battles for their realization. After the process of constitutionality and constitutional movements began, the universality of human rights and freedoms came to the fore. Namely, it is from the time of Bill of Rights in 1215 until today. In a modern sense human rights are becoming universal which are already guaranteed by the UN Charter and the European Convention on Human Rights. Especially Macedonia, as a candidate country for membership in the European Union, is fulfilling even new additions. Humanity and the Rights of the Child were created on the basis of the French Revolution, which was founded on August 26, 1789, for the purpose of demonstrating the cause of democracy and freedom. 1789 - Declaration of Human and Citizen Rights are published by the French Revolution. Accepted by the French National Assembly on August 26, 1789 Adopted by the French Mankind and Advocates in 1789, Adopted by the French Constitution in 1791. Humanity and Human Rights Consciousness is a human being and is made of 17 articles. Bunlar; Human rights are based on different rules and principles. Freedom of expression, property, security and the right to freedom of expression should not be expressed in the words of the citizens. 1789 Declaration of Human and Citizen Rights, The statement of the 16th article of the article on the existence of freedom, the meaning of the rights of the right and the right of the righteous, is expressed in a comprehensive way. In accordance with the idea of a nation-state that emerged from this, the Macedonian state started to make a new constitution in 1991 after declaring its independence and aimed to guarantee both the spirit of the Declaration and the universal nature of human rights with the constitution.